Is Duolingo Media Effective? An Experimental Study on Increasing Student Interest in Arabic Learning - Adira, Wafa' Rizqiyya; Hamdun, Dudung; Ramadhan, Ahmad Rizki; Hasna, Tsania Sausan (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This study aims to determine whether Duolingo application effectively increases students’ interest and how much it increases student’s interest in Arabic learning. This study used a quantitative approach with experimental methods (one group pretest posttest design), and the population was class IX students of MTs Al Riyadhul Jannah. The sample in this study were students of class IX C, totaling 21 students using purposive sampling technique. Data collection was obtained through observation, interviews, questionnaires, and documentation. Data hypothesis testing was carried out through paired sample t-test and N gain test. The results showed a significance value of 0,003 < 0,05 that H0 was rejected and Ha was accepted, also the N gain percent value was 26,8198. So, Duolingo application is effective in increasing students’ interest in Arabic language learning and there is an increase in interest by 26,82%. The main contribution in this study is to apply new teaching media based on online games that are expected to increase students’ interest in Arabic learning.